Genome sequencing identifies rare tandem repeat expansions and copy number variants in Lennox–Gastaut syndrome. Issue 3 (14th September 2021) - Qaiser, Farah; Sadoway, Tara; Yin, Yue; Zulfiqar Ali, Quratulain; Nguyen, Charlotte M; Shum, Natalie; Backstrom, Ian; Marques, Paula T; Tabarestani, Sepideh; Munhoz, Renato P; Krings, Timo; Pearson, Christopher E; et al.
Abstract: Epilepsies are a group of common neurological disorders with a substantial genetic basis. Despite this, the molecular diagnosis of epilepsies remains challenging due to its heterogeneity. Studies utilizing whole-genome sequencing may provide additional insights into genetic causes of epilepsies of unknown aetiology. Whole-genome sequencing was used to evaluate a cohort of adults with unexplained developmental and epileptic encephalopathies ( n = 30), for whom prior genetic tests, including whole-exome sequencing in some cases, were negative or inconclusive. Rare single nucleotide variants, insertions/deletions, copy number variants and tandem repeat expansions were analysed. Seven pathogenic or likely pathogenic single nucleotide variants, and two pathogenic deleterious copy number variants were identified in nine patients (32.1% of the cohort). One of the copy number variants, identified in a patient with Lennox–Gastaut syndrome, was too small to be detected by chromosomal microarray techniques. We also identified two tandem repeat expansions with clinical implications in two other patients with Lennox–Gastaut syndrome: a CGG repeat expansion in the 5′untranslated region of DIP2B, and a CTG expansion in ATXN8OS (previously implicated in spinocerebellar ataxia type 8). Three patients had KCNA2 pathogenic variants. One of them died of sudden unexpected death in epilepsy. The other two patients had, in addition to a KCNA2 variant, a second de novo variant impacting potential epilepsy-relevant genes ( KCNIP4 and UBR5 ). Overall, whole-genome sequencing provided a genetic explanation in 32.1% of the total cohort. This is also the first report of coding and non-coding tandem repeat expansions identified in patients with Lennox–Gastaut syndrome. This study demonstrates that using whole-genome sequencing, the examination of multiple types of rare genetic variation, including those found in the non-coding region of the genome, can help resolve unexplained epilepsies. Abstract : See Mills and Sisodiya (doi:10.1093/braincomms/fcab280 ) for a scientific commentary on this article. Using whole-genome sequencing, Qaiser et al. identified rare genetic variants in a cohort of adults with unexplained developmental and epileptic encephalopathies ( n = 30), for whom prior genetic tests were inconclusive. This is also the first report of coding and non-coding tandem repeat expansions identified in patients with Lennox–Gastaut Syndrome. Graphical Abstract: Video Abstract: